2018
DOI: 10.1136/bcr-2017-222621
|View full text |Cite
|
Sign up to set email alerts
|

Phaeochromocytoma found on cardiovascular magnetic resonance in a patient presenting with acute myocarditis: an unusual association

Abstract: Myocarditis is inflammation of the cardiac muscle. The symptoms, signs and basic investigation findings can mimic that of myocardial infarction. The most common cause is infection (most commonly viral). Cardiovascular magnetic resonance (CMR) is the gold standard non-invasive diagnostic test for potential acute myocarditis as it allows assessment of myocardial oedema and scar. A man aged 25 years was admitted with chest pain, dizziness, headache, palpitations and sweating. His troponin was mildly positive. A C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Catecholamine myocarditis as a complication of PPGLs has been reported since decades [71,72]. The diagnosis of PPGL-induced myocarditis was based on the clinical picture, ECG changes [73], histopathological features through either endomyocardial biopsy [74] or autopsy [71], and cardiac magnetic resonance imaging (C-MRI) [61]. In 1966, Van Vliet et al reported that 15 (58%) of 26 patients who died due to pheochromocytoma disclosed disseminated focal myocardial lesion which the authors designated "active catecholamine myocarditis" [71].…”
Section: Ppgls and Myocarditismentioning
confidence: 99%
See 3 more Smart Citations
“…Catecholamine myocarditis as a complication of PPGLs has been reported since decades [71,72]. The diagnosis of PPGL-induced myocarditis was based on the clinical picture, ECG changes [73], histopathological features through either endomyocardial biopsy [74] or autopsy [71], and cardiac magnetic resonance imaging (C-MRI) [61]. In 1966, Van Vliet et al reported that 15 (58%) of 26 patients who died due to pheochromocytoma disclosed disseminated focal myocardial lesion which the authors designated "active catecholamine myocarditis" [71].…”
Section: Ppgls and Myocarditismentioning
confidence: 99%
“…These changes cannot be explained by the effects of hypertension. Cases with clear findings consistent with PPGL-induced TS have been published with the diagnosis myocarditis (Table 1) [58,61]. Based on patchy late gadolinium enhancement on C-MRI, some cases were deemed as PPGL-induced myocarditis [61].…”
Section: Ppgls and Myocarditismentioning
confidence: 99%
See 2 more Smart Citations
“…CMR imaging, if done early during TS, may reveal LGE in the affected hypokinetic segments in about one third of cases[ 33 ]. However, the signal intensity of LGE in TS is less than that of MI and myocarditis and the LGE is patchy in appearance and in some cases described as myocarditis[ 34 , 35 ]; chemical (neuro-mediated by norepinephrine) myocarditis may be a feature of TS[ 36 ] and may explain the patchy LGE findings in TS; it is usually reversible (neurogenic stunning). Moreover, the most important sign, which challenges MI in TS, is the histo-pathological finding of contraction band necrosis, which is distinct from coagulation necrosis seen in MI[ 37 ].…”
Section: Evidence For That Takotsubo Syndrome Is Not a MImentioning
confidence: 99%